Practical forensic analysis of artifacts on iOS and Android devices : investigating complex mobile devices - Moreb, Mohammed (Apress, 2022)
Leverage foundational concepts and practical skills in mobile device forensics to perform forensically sound criminal investigations involving the most complex mobile devices currently available on the market. Using modern tools and techniques, this book shows you how to conduct a structured investigation process to determine the nature of the crime and to produce results that are useful in criminal proceedings. You'll walkthrough the various phases of the mobile forensics process for both Android and iOS-based devices, including forensically extracting, collecting, and analyzing data and producing and disseminating reports. Practical cases and labs involving specialized hardware and software illustrate practical application and performance of data acquisition (including deleted data) and the analysis of extracted information. You'll also gain an advanced understanding of computer forensics, focusing on mobile devices and other devices not classifiable as laptops, desktops, or servers. This book is your pathway to developing the critical thinking, analytical reasoning, and technical writing skills necessary to effectively work in a junior-level digital forensic or cybersecurity analyst role. What You'll Learn Acquire and investigate data from mobile devices using forensically sound, industry-standard tools Understand the relationship between mobile and desktop devices in criminal and corporate investigations Analyze backup files and artifacts for forensic evidence Who This Book Is For Forensic examiners with little or basic experience in mobile forensics or open source solutions for mobile forensics. The book will also be useful to anyone seeking a deeper understanding of mobile internals.